The Theory Of Human Capital And Its Directions - Sharipov Mirzoxid Latifovich (Periodica Journal, 2024)
This article analyzes the essence, characteristics and types of human capital, the development of human capital theories, stages, and priorities of its development.
Keywords: capital; human capital; micro level